2021
DOI: 10.3390/life11080856
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of HepG2 and HepaRG Systems through the Glass of Acetaminophen-Induced Toxicity

Abstract: Investigation of drug-induced liver injuries requires appropriate in vivo and in vitro toxicological model systems. In our study, an attempt was made to compare the hepatocarcinoma HepG2 and the stem cell-derived HepaRG cell lines both in two- and three-dimensional culture conditions to find the most suitable model. Comparison of the liver-specific characteristics of these models was performed via the extent and mechanism of acetaminophen (APAP)-induced hepatotoxicity. Investigating the detailed mechanism of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
5
1
2
Order By: Relevance
“…It is reported in the literature that IC 50 values of APAP-treated 2D mouse hepatocytes ranged from 3.8 to 20 mM (Fey & Wrzesinski, 2012), consistent with our findings for the TAMH cell line. HepG2 cells in this study appeared to be more sensitive to APAP-treatment (IC 50 < 10 mM) than reported in literature, where values of $10-30 mM for 2D cultured HepG2 cells were determined (Aritomi et al, 2014;L} orincz et al, 2021). This discrepancy could be attributed maximal plasma concentrations (c max ) were 2.8 (Siegmund et al, 2015) and 1.4 μM (Ferron et al, 2002), respectively.…”
Section: Discussioncontrasting
confidence: 66%
“…It is reported in the literature that IC 50 values of APAP-treated 2D mouse hepatocytes ranged from 3.8 to 20 mM (Fey & Wrzesinski, 2012), consistent with our findings for the TAMH cell line. HepG2 cells in this study appeared to be more sensitive to APAP-treatment (IC 50 < 10 mM) than reported in literature, where values of $10-30 mM for 2D cultured HepG2 cells were determined (Aritomi et al, 2014;L} orincz et al, 2021). This discrepancy could be attributed maximal plasma concentrations (c max ) were 2.8 (Siegmund et al, 2015) and 1.4 μM (Ferron et al, 2002), respectively.…”
Section: Discussioncontrasting
confidence: 66%
“…Hücrelerin yaklaşık olarak %90 oranında yüzeyi kaplaması beklendikten sonra adhezyon için 24 saat inkübe edilmiştir. Sonra, hücreler 20mM APAP ile 4 saat muamele edilmiştir [30,31]. APAP verilişinden sonra 4-OHFBA'nın 31,25µM, 62,5µM, 125µM ve 250µM dozları kuyucuklara eklenerek 24. ve 48. saatlerde hücre canlılığı değerlendirilmiştir [30].…”
Section: Hücre Kültürü Prosedürü Ve Apap Uygulaması (Cellunclassified
“…Sonra, hücreler 20mM APAP ile 4 saat muamele edilmiştir [30,31]. APAP verilişinden sonra 4-OHFBA'nın 31,25µM, 62,5µM, 125µM ve 250µM dozları kuyucuklara eklenerek 24. ve 48. saatlerde hücre canlılığı değerlendirilmiştir [30]. Tedavi grupları, kontrol grupları ile kıyaslanmıştır.…”
Section: Hücre Kültürü Prosedürü Ve Apap Uygulaması (Cellunclassified
“…Approximately 5-10% of APAP is oxidised by CYP450s into N-acetyl-p-benzoquinone imine (NAPQI) which is detoxified with glutathione (GSH) upon conjugation. It is thought that the toxicity of APAP is directly linked to the binding of NAPQI to mitochondrial proteins (Lőrincz et al, 2021). To demonstrate the improved function of MTs, HepG2 cells grown in a 2D monolayer were compared to 3D MTs before and after treatment with 30mM APAP where APAP was used to induce cell death.…”
Section: -Results and Discussionmentioning
confidence: 99%